Healthcare Cost Savings Estimator Tool for Chronic Disease Self-Management Program (CDSMP): A New Tool for Program Administrators and Decision Makers - SangNam eAhn; SangNam eAhn; Matthew Lee eSmith; Mary eAltpeter; Lindsey ePost; Marcia Gail Ory (Frontiers Media S.A., 2015)
*